2003
DOI: 10.1016/s0873-2159(15)30690-5
|View full text |Cite
|
Sign up to set email alerts
|

O ruído e o aparelho respiratório

Abstract: Noise-induced pulmonary pathology is still an issue that is regarded with much suspicion despite the significant body of evidence demonstrating that acoustic phenomena target the respiratory tract. The goal of this review paper is threefold: a) to describe acoustic phenomena as an agent of disease, and the inadequacies of current legislation regarding noise-induced, non-auditory pathology; b) to trace how the interest in noise-induced pulmonary pathology emerged within the scope of studies on vibroacoustic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Noise is also suggested to have effects on various organs and systems such as gastrointestinal, [ 2 ] respiratory, [ 3 ] immune, [ 4 ] reproductive, [ 5 ] and neurogenic system. [ 6 ] Among all, the impact of noise on the cardiovascular system is particularly prominent, according to several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Noise is also suggested to have effects on various organs and systems such as gastrointestinal, [ 2 ] respiratory, [ 3 ] immune, [ 4 ] reproductive, [ 5 ] and neurogenic system. [ 6 ] Among all, the impact of noise on the cardiovascular system is particularly prominent, according to several studies.…”
Section: Introductionmentioning
confidence: 99%
“…The present study further revealed that subjects exposed to LFN had decreased MPT and increased s/z ratio (higher than 1.40). The studies conducted by Mendes et al 60 61 62 and Alves-Pereira et al 63 also reported these results. The current study also revealed that hoarse voice quality may be due vocal abuse and unhealthy dietary habits, which is in line with the study by Castelo Branco.…”
Section: Discussionmentioning
confidence: 63%
“…It is reported acoustics can pose impacts on the gastrointestinal tract [ 29 ], respiratory system [ 30 ], immune system [ 31 ], reproductive system [ 32 ], nervous system [ 33 ], and other systems. Among them, the influence on the cardiovascular system is particularly prominent.…”
Section: Discussionmentioning
confidence: 99%